Solvation of barium atoms and singly charged cations in acetonitrile clusters - Taccone, Martín Ignacio (2018)
The size distributions of neutral and cationic Bax(CH3CN)n (x = 0, +1; n ≤ 7) clusters, as produced by a standard laser vaporization-supersonic expansion pick-up source, were determined from molecular beam experiments. The size distribution for cations is in the range of n = 1-7, whereas only the n = 1 complex is observed for neutral clusters, and these two features are unaffected by the variables controlling the performance of the cluster source. The distinct behavior is compatible with the expected charge-dipole interactions in the ionic species, which are stronger than the dipole induced-dipole interactions at play in neutral clusters, and it is corroborated by the relative magnitude of the theoretical successive binding energies (SBEs) for the lowest-lying isomers of cationic and neutral clusters with n = 1-5, as computed at the density functional theory level. The theoretical results also allow for the rationalization of the bimodal Ba+(CH3CN)1-7 size distribution, featuring an apparent minimum at n = 3, in terms of chiefly 6s-5d σ hybridization of the Ba+ ions, which ultimately leads to a relatively small third SBE for the Ba+(CH3CN)3 complex, as compared to those for n = 1, 2, and 4. Additional Born-Oppenheimer molecular dynamics simulations on the Ba+(CH3CN)2-4 clusters suggest that all of the ligands are coordinated to the Ba+ ion and prevent considering completion of the first solvent shell as responsible for the bimodal size distribution.